El Excentrico, 1966-08-20 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
August 20, 1966 [20 de Agosto de 1966]. No Volume or issue number. Cover has a headshot of a Mary D. Rogers in formal attire, with headline, "Mary D. Rogers joins Excentrico Staff."